Análise da concentração no mercado farmacêutico brasileiro no período de 2010 a 2014 - Molina, Marcel Franco (2024)
This dissertation investigated the process of industrial concentration in the Brazilian pharmaceutical market, from the drug industry offered by various national and international laboratories operating in Brazil for the period 2010 to 2014. We analyzed the market power from index classic concentration such as the concentration ratio, Herfindahl Hirschmann index, Hall Tiedman index and the Theil entropy index. Note for the results of the tables of concentration indices, the pharmaceutical industry both in relation to the total products offered in the market as c ompared to manufactured products showed a slight concentration in view of the values obtained for the respective indices of industrial concentration. Was obtained from the indices of concentration ratio CR5 and CR10, a very moderate concentration, while th ere was a slight decrease in concentration for the group of the twenty largest companies, between Dec 2010 compared to Dec / 2014. Furthermore, concerning concentration indices in the drug market, both in units and dollars, it was observed that the total m arket concentration in dollars slightly increased in 2014 compared to 2010 according to the HHI, HTI indices, and Theil entropy index. However, Table 5 showed an increase in concentration in 2014 compared to 2010 in the HTI and Theil entropy concentration indices and a slight reduction in HHI in 2014 compared to the year 2010 . Based on the results of the econometric model estimates, it was found that the explanatory variables Net Revenue and Net Worth were statistically significant at the 1% significance level. However, in the econometric models analyzed in this research, no statistically significant evidence was observed for the relationship between the dependent variable and the explanatory variables indicating industrial concentration, such as market share, HHI, HTI, and entropy.